Development of In Vitro–In Vivo Correlation for Extended‐Release Niacin After Administration of Hypromellose‐Based Matrix Formulations to Healthy Volunteers. Issue 11 (24th September 2014) - Kesisoglou, Filippos; Rossenu, Stefaan; Farrell, Colm; Van Den Heuvel, Michiel; Prohn, Marita; Fitzpatrick, Shaun; De Kam, Pieter‐Jan; Vargo, Ryan
<x xml:space="preserve">Abstract</x> Development of in vitro–in vivo correlations (IVIVCs) for extended‐release (ER) products is commonly pursued during pharmaceutical development to increase product understanding, set release specifications, and support biowaivers. This manuscript details the development of Level C and Level A IVIVCs for ER formulations of niacin, a highly variable and extensively metabolized compound. Three ER formulations were screened in a cross‐over study against immediate‐release niacin. A Multiple Level C IVIVC was established for both niacin and its primary metabolite nicotinuric acid (NUA) as well as total niacin metabolites urinary excretion. For NUA, but not for niacin, Level A IVIVC models with acceptable prediction errors were achievable via a modified IVIVC rather than a traditional deconvolution/convolution approach. Hence, this is in contradiction with current regulatory guidelines that suggest that when a Multiple Level C IVIVC is established, Level A models should also be readily achievable. We demonstrate that for a highly variable, highly metabolized compound such as niacin, development of a Level A IVIVC model fully validated according to agency guidelines may be challenging. However, Multiple Level C models are achievable and could be used to guide release specifications and formulation/manufacturing changes. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3713–3723, 2014